Innovations. Market and Social Aspects - Ornarowicz, Urszula (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
Areas of research in economics and management science become increasingly close – they overlap and become very similar. New events, new products of people’s actions, new patterns of behaviour arise with a pace unknown before. Institutionalisation of these phenomena aimed at their broad codification also takes on new forms. We live in an age of ubiquitous innovativeness. Naturally, the question arises: should innovations be perceived in the same way as in the past? Are there any new types of innovations that have appeared lately? Are the current definitions of market and social innovations still up to date? The aim of the article is to present a change in approach to innovations over time, with particular focus on their market and social aspects. The author attempts to answer the following questions: how did technological progress visible in the networking of economy influence the understanding of social innovations, what is the role of social production and exchange which replace gradually market exchange, in the social innovation definition, to what extent is the cooperation within a community in the virtual space characteristic of a special class of social innovation? The research method used by the author is based on literature studies on innovations and on the economics of cooperation (access, sharing, co‑use). It comprises an analysis of different concepts of innovation, in particular different definitions of the name, an analysis of different approaches to cooperation economics, comparisons of the obtained results, and conclusions formulation. The approach to innovation changes over time – from a technical, social and market approach to a differently understood today social approach. Contemporary, the criteria for innovation “society” are different. The understanding of innovation is influenced by the increased role of social production and exchange at the expense of market exchange. The networking of the information economy significantly strengthens the social aspect of innovation. Cooperation within a community, including co‑creation of goods, access to them, their co‑use and sharing, is an extreme example of the advantage of the social dimension of innovation over its market aspect.